Comparative efficacy of Albendazole, Fenbendazole and Levamisole against gastrointestinal nematodiasis in cattle of Bangladesh - Islam, Monirul; Islam, Siddiqul; Howlader, Matiar; Lucky, Nasrin (International Journal of Biological Research, 2015)
Out of 52 cattle 30 were heavily infested with different gastrointestinal nematodes which were identified by faecal examination. Among 30 cattle 20 were selected randomly and divided into four groups (A, B, C and D). Group D was kept as infected control group. Group A, B and C were treated with patent drug Albendazole (Helmex-vet® 600 mg/Tab) 7.5, Fenbendazole (Peraclear® 250 mg/bolus) 7.5 and Levamisole (Ralnex® 708 mg/bolus) 7.5 mg/kg body weight orally for the determination of effects on blood parameters. Before trials with Helmex-vet®, Peraclear® and Ralnex® initial total egg count of gastrointestinal helminths and haematological parameters were examined and recorded. During the experimental period the faecal samples were examined on 7th, 14th, 21st and 28th day. Haematological parameters (TEC, Hb, ESR, TLC and PCV) were also examined from 7 to 28 days for the determination of effects of Helmex-vet®, Peraclear® and Ralnex®. A significant reduction of EPG of gastrointestinal nematodes were found on 7th, 14th, 21st and 28th day of Helmex-vet® (46.91%, 72.84%, 84.44% and 93.58%), Peraclear® (46.67%, 71.67%, 83.33% and 90.56%) and Ralnex® (49.27%, 72.82%, 93.93% and 85.80%) of group A, B and C respectively. The EPG of untreated group were significantly increased about 3.37%, 6.75%, 8.13% and 9.69% on 7th, 14th, 21st and 28th day respectively. After treatment with Helmex-vet®, Peraclear® and Ralnex®, TEC, Hb, TLC and PCV were increased and ESR were decreased in cattle. On the other hand, TEC, Hb, TLC and PCV were decreased and ESR was increased significantly (p<0.05) in untreated group.